PERIODISASI POLITIK HUKUM PIDANA ISLAM ACEH SEJAK TAHUN 2000-2018 - Bahrum, Syamsuddin (IAIN Langsa, 2018)
Periodization of Islamic criminal politics in Aceh since 2000-2018 is the dynamics of the politics of Islamic criminal law in the Acehnese society in the application of Islamic law in Aceh Province carried out under the principle of lex specialis derogaatlege generalis. Periodization of Islamic criminal politics in Aceh from 2000-2018 with the issuance of Law No. 18 of 2001 concerning Special Autonomy for the Special Province of Aceh as the Province of Nanggroe Aceh Darussalam which was implemented in Qanun Number 11 of 2002 concerning the Implementation of Islamic Sharia in the Aqeedah Islam, Qanun Number 12 of 2003 concerning Khamar and the like, Qanun Number 13 of 2003 concerning Maisir (Gambling), Qanun Number 14 of 2003 concerning Seclusion (Mesum) and Qanun Number 4 of 2004 concerning Management of Zakat. The politics of Islamic criminal law has developments with the Law of the Republic of Indonesia Number 11 of 2006 concerning Aceh Government. The mandate of the Republic of Indonesia Law Number 11 of 2006 concerning the Government of Aceh in the application of Islamic criminal law is implemented through Qanun Number 6 of 2014 concerning Jinayat Law and Qanun Number 7 of 2013 concerning Jinayat Procedure Law which implements' Uqubat Cambuk on the mosque yard and / or open field has been running safely, orderly, unpretentious, effective and efficient. However, the period 20 is December 13, 2013. In this periodization the application of Islamic criminal law in accordance with Qanun Number 6 of 2014 concerning Jinayat Law and Qanun Number 7 of 2013 concerning Jinayat's Procedure Law runs smoothly and effectively. Periodization of 2017 until now, the political dynamics of Islamic criminal deterioration occurred with the issuance of Aceh Governor's Regulation Number 05 of 2018 concerning the Implementation of Jinayat's Laws that moved 'Uqubat Cambuk open space held in the courtyard of the mosque and / or open field. effectively and efficiently moved its location to the community / detention center / detention center.